Impact of policy incentives on adoption of electric vehicles in South Korea - Hyunseok Kim (Korea Development Institute (KDI), 2024)
South Korea's strategies for deploying battery electric vehicles (BEVs) primarily include providing purchase subsidies and expanding charging infrastructure. An empirical analysis of new vehicle registrations from 2019 to 2022 shows that investing in charging facilities is more costeffective than offering purchase incentives for increasing BEV adoption. To achieve a higher share of BEVs, a stronger policy focus on improving the charging network is necessary to stimulate overall demand for BEVs.
Keywords: 330; Electric vehicle; purchase; subsidy; public spending; sustainable mobility; impact analysis; South Korea; Elektrofahrzeug; Kauf; Subvention; Öffentliche Ausgaben; Nachhaltige Mobilität; Wirkungsanalyse; Südkorea